Assessment of Carotid Intraplaque Neovascularization Using Superb Microvascular Imaging in High Risk of Stroke Individuals: Results From a Community-Based Study - Wang, Ying; Yao, Ming; Zou, Mi; Li, Shengde; Ge, Zhitong; Hong, Yuehui; Cai, Siman; Wang, Hongyan; Li, Jianchu (Frontiers in Neurology, 2019)
Background: Improved stroke risk stratification may improve stroke prevention. We aimed to study the value of a novel Doppler method, superb microvascular imaging (SMI), in correlating plaque thickness and evidence of intra-plaque neovascularization with a history stroke and TIA involving any cerebrovascular territory among community residents considered at high stroke risk. Methods: We selected dwellers aged at least 40 years from the Donghuashi community in China who had at least 3 stroke risk factors or a history of stroke or TIA, and carotid plaque thickness of at least 15mm (but without heavy calcification) and no history of carotid endarterectomy or stenting. In this cross-sectional study each subject underwent carotid plaque examination with standard ultrasound and SMI. SMI evidence of plaque neovascularization was categorised as none or mild (Grade 1) or moderate or marked (Grade 2) and correlated with past history of stroke or TIA. Results: A total of 131 individuals (mean age 69±8 years, 63% male) met the study inclusion criteria. SMI revealed no or mild neovascularization in 74 subjects (56.5%) and moderate or marked neovascularization in 57 subjects (43.5%). Subjects with moderate or marked neovascularization were more likely to have a history of any territory stroke or TIA, 43.9% versus 17.6% (P=0.001). Multivariate logistic regression analyses showed a thicker plaque (odds ratio: 2.272, 95% CI:1.351-3.822, P=0.002) and a history of stroke or TIA (odds ratio: 4.017, 95% CI:1.719-9.387, P=0.001) significantly correlated with evidence of moderate to marked intra-plaque neovascularization. Conclusions: Moderate to marked intra-plaque neovascularization detected by SMI was more likely in subjects with a history of any territory stroke or TIA. This indicates a potential new role of SMI in stratifying future risk of stroke or other arterial disease complications.